GAMBARAN PERSEPSI PASIEN TERHADAP PELAKSANAAN PERILAKU CARING DALAM PELAYANAN KEPERAWATAN DI RUANGAN RAWAT INAP BEDAH RSUD SOLOK - Netty Herawati (Ensiklopedia Social Review, 2020)
The quality of health services and the image of a hospital is largely determined by the role of nurses, because 90% of health services in hospitals are provided by nurses. in providing quality nursing services can be applied by using caring behavior in providing nursing care to clients. Caring is special and depends on the relationship between the nurse and the client, where caring facilitates the nurse's ability to recognize the client so the nurse can find out the client's problem and find and implement a solution. The survey conducted by researchers at Solok District Hospital on evaluating the quality of nursing services to patient satisfaction in the inpatient office of Solok Hospital obtained a surgical room with 42% good, and 58% less good. The fact that was found in the field more than half (59.4%) of respondents had a negative perception of the implementation of nurses caring behavior in the operating room in Solok Hospital and more than half (40.6%) of respondents had a positive perception of the implementation of nurses caring behavior in the room inpatient surgery. It is expected that all nurses, especially nurses in the room can carry out caring behaviors to all patients optimally because caring behavior by nurses can optimally affect how a person or patient thinks, feels and behaves in dealing with others, so as to provide patient satisfaction towards nursing services.